1990
DOI: 10.1002/pola.1990.080280921
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion polymerization of styrene in polar solvents. IV. Solvency control of particle size from hydroxypropyl cellulose stabilized polymerizations

Abstract: SynopsisChanging solvent has a dramatic effect on the outcome of HPC stabilized dispersion polymerization of styrene in polar solvents. In methoxyethanol/ethanol mixtures, particle size varies from essentially infinity for unstabilized reactions (below 30% ethanol) to about 3 microns in ethanol. In a series of n-alcohols, there was a maximum in particle size at intermediate chain length particle size increased from 2 microns in methanol to 8.3 microns in pentanol, then decreased again to 1 micron in octadecano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 13 publications
5
74
0
Order By: Relevance
“…28,29 The molecular weight increases but with a gradually reduced rate as the conversion increases. These results suggest that the gel effect (the so called solid phase polymerization) [5][6][7] is operative.…”
Section: Resultsmentioning
confidence: 87%
“…28,29 The molecular weight increases but with a gradually reduced rate as the conversion increases. These results suggest that the gel effect (the so called solid phase polymerization) [5][6][7] is operative.…”
Section: Resultsmentioning
confidence: 87%
“…Larger particles were synthesized using DMF/water mixtures. Paine 35 and Baines et al 36 observed that the particles in ethanol compared to those in methanol in dispersion polymerization of St with poly(vinylpyrrolidone) or poly(2-dimethylamino) ethyl methacrylate-b-methyl methacrylate as a stabilizer were larger. Ober et al 34 noted that particle size could be broadly correlated with the solubility parameter of the initial polymerization mixture, though quantitative correlations between different solvent types could not be observed.…”
Section: Effects Of Solvent Compositionmentioning
confidence: 97%
“…7 During the past 15 years, there has been a considerable interest in generalizing these results to more polar solvents as the continuous phase, by which the range of monomers that can be polymerized using this method have been greatly expanded. Hydroxypropyl cellulose (HPC), 23 poly(acrylic acid) (PAA), 24 and polyvinylpyrrolidone (PVP) 10,11,25 are the most frequently used stabilizers in polar media. The relative extent of the interaction between the reaction medium, the stabilizer, and the polymer that is being produced is considered to be one of the key factors that controls the final particle size.…”
Section: Introductionmentioning
confidence: 99%